THE INFLUENCE OF COMPETENCE, CAREER DEVELOPMENT, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN SUKUN DISTRICT - Nirmawati, Mila; Hadiyati, Ernani; Farhan, Djuni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The purpose of this research is to examine and analyze the influence of competence, career development, and work motivation on employee performance; to examine and analyze the influence of competence on employee performance; to examine and analyze the influence of career development on employee performance; and to examine and analyze the influence of work motivation on employee performance. This study employs an explanatory research method. The sample consists of 62 employees, using a census sampling technique. The statistical analysis used is multiple regression analysis. The results show that competence, career development, and motivation significantly influence performance. This indicates that the higher the level of competence possessed by civil servants, the better their performance will be in carrying out their duties and functions. A structured and clear career development program improves employee performance. Motivated employees demonstrate higher dedication, commitment, and work spirit in completing their tasks, thereby resulting in better performance. Competence has a significant effect on employee performance, meaning that employees with strong competencies are proven to deliver better performance in terms of both quality and quantity of work. Career development significantly affects employee performance, indicating that a clear, structured, and fair career development system in Sukun District successfully creates positive perceptions and provides direction for employees in planning their professional future. The clarity of career paths and transparency in the promotion process encourage employees to demonstrate optimal performance and continuously develop their potential. Work motivation has a significant effect on employee performance, meaning that employees with high work motivation are able to create strong drive to work optimally and achieve the set performance targets.